Hybrid Regimes and Political (Dis)Order - Ficek, Ryszard (Historia i Polityka, 2023)
This paper studies the concept of “hybrid regimes”, not so much in defining and authenticating their functionality but, above all, to exhibit them as so-called “partial” constitutional concepts. Articulating the tensions, divergences, and antagonisms characteristic of these regimes, as well as highlighting the blurring boundaries between democratic systems and authoritarianism “with adjectives”, emphasizes the importance of the examined issues. The author introduces an alternative conceptualization and typology of hybrid regimes and a configurational approach. Instead of placing political regimes on a linear continuum – from authoritarianism to democracy – multidimensional solutions facilitating an alternative typology of the analyzed concepts have been exposed. The configuration approach, however, provides an analytically valuable way to evaluate and integrate hybrid regimes with other classification schemes. Such innovations, therefore, help alleviate conceptual confusion in the literature. Moreover, deepening the understanding of the concept of hybrid regimes, along with emphasizing its conceptual ambiguities and complexity – especially concerning the “politically correct” discourse on the current problems of fragile and politically unstable states – is necessary to better understand the complex and confusing nature of modern regimes of power frequently operating in the most politically unstable regions of the contemporary world.